Integrative Population Genomics Reveals Niche Differentiation and Gene Flow in Chinese Sclerophyllous Oaks (Quercus Sect. Ilex) - Miao-Miao Ju; Ming Yue; Gui-Fang Zhao (Plants)
Elucidating the coexistence mechanisms of rapidly diverging species has long been a challenge in evolutionary biology. Genome-wide polymorphic loci are expected to provide insights into the speciation processes of these closely related species. This study focused on seven Chinese sclerophyllous oaks, represented by Quercus spinosa, Quercus aquifolioides, Quercus rehderiana, Quercus guyavifolia, Quercus monimotricha, Quercus semecarpifolia, and Quercus senescens, employing 27,592 single-nucleotide polymorphisms to examine their phylogenetic relationships at the genomic level. Combined with genetic structure analysis, phylogenetic trees revealed that the genetic clustering of individuals was influenced by both geographic distance and ancestral genetic components. Furthermore, this study confirmed the existence of reticulate evolutionary relationships among the species. Frequent gene flow and introgression within the seven species were primarily responsible for the ambiguous interspecies boundaries, with hybridization serving as a major driver of reticulate evolution. Additionally, the seven species exhibited distinct differences in niche occupancy. By reconstructing the climatic adaptability of ancestral taxonomic units, we found that the climatic tolerance of each species displayed differential responses to 19 climatic factors. Consequently, ecological niche differentiation and variations in habitat adaptation contributed to the preservation of species boundaries. This study provides a comprehensive understanding of the speciation processes in rapidly diverging genera and underscores the significance of both genetic and ecological factors in the formation and maintenance of species boundaries.